Post-Pandemic Possibilities in Mandel’s Station Eleven - Sharma, Prakash (Journal of NELTA Gandaki, 2024)
This paper explores how human self-centeredness and indifference to the ecological balance bring human existence into crisis inviting different apocalypses; and examines the post-pandemic possibilities in Emile St. John Mandel’s novel Station Eleven. The text discusses the crisis caused by a pandemic killing ninety percent of the human population. This study concentrates on the hectic life of the characters before the pandemic, the critical life during the pandemic and the post-apocalyptic life freed from machines and material greed. It analyses how people’s material greed and negligence on harmonious human-nonhuman relations result in the crisis. To bring the crisis of the pandemic into normality, the writer uses art in different forms. In other words, this study examines human experiences in the face of extreme loss and shows the importance of art in adversity. The focus of the study is to show how bleakness, pessimism and adversity dominate the narrative and simultaneously unfold certain events and situations that signal optimism in the novel. This research is based on the library study and uses data from both primary and secondary sources. The critical insights of Lawrence Buell and Val Plumwood about human self-centeredness and interdependence between the biotic and abiotic world are the theoretical ideas for textual analysis of the primary text. It concludes that the presentation of the horrific situation in the novel is for creating eco-consciousness and the situations of possibilities are for the generation of hope in crisis. This research work promotes eco-consciousness and sustains hope even in critical situations.